The Influence of Accounting Knowledge, Business Experience, and Business Mentoring on The Use of Accounting Information in MSMEs in Palu City - Cahya Bilqis Syahrani; Muhammad Ilham Pakawaru; Ernawaty Usman; Muliati Muliati (SAFE-Network, 2026)
This study investigates how far accounting knowledge, business experience, business mentoring influence the use of accounting information MSMEs in Palu City. This study employs a quantitative approach using a survey method, in which data were collected through structured questionnaires distributed to respondents. The collected data were then analyzed using multiple linear regression techniques to examine the relationships between variables. The research subjects consist of 35 Micro, Small, and Medium Enterprises (MSMEs) operating in Palu City, which were selected based on purposive sampling criteria to ensure their relevance to the research objectives. Furthermore, data processing and statistical analysis were carried out using IBM SPSS Statistics version 27. The study shows that accounting knowledge positively and significantly contributes to the use of accounting information, indicating that a stronger understanding of accounting concepts encourages MSME actors to utilize financial data more effectively. In contrast, prior entrepreneurial business experience does not show a significant influence, suggesting that business longevity does not necessarily translate into better use of accounting information without adequate financial literacy. Meanwhile, business mentoring demonstrates a significant, revealing the essential role of external support in fostering better financial practices. These findings imply that efforts to enhance accounting information is used by MSMEs should focus on strengthening accounting knowledge and providing continuous business mentoring.